THE DEVELOPMENT OF TOWN-SHIELDS’ PLANNING IN BISHOPRICS OF LIVONIA DURING THE 13TH–14TH CENTURIES - Ozola, Silvija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Traditions of the Christianity centres’ formation can be found in Jerusalem’s oldest part where instead of domestic inhabitants’ dwellings the second king of Israel (around 1005 BC–965 BC) David built his residence on a top of the Temple Mount surrounded by deep valleys. His fortress – the City of David protected from the north side by inhabitants’ stone buildings on a slope was an unassailable public and spiritual centre that northwards extended up to the Ophel used for the governance. David’s son, king of Israel (around 970–931 BC) Solomon extended the fortified urban area where Templum Solomonis was built. In Livonia, Bishop Albrecht obtained spacious areas, where he established bishoprics and towns. At foothills, residential building of inhabitants like shields guarded Bishop’s residence. The town-shield was the Dorpat Bishopric’s centre Dorpat and the Ösel–Wiek Bishopric’s centre Haapsalu. The town of Hasenpoth in the Bishopric of Courland (1234–1583) was established at subjugated lands inhabited by the Cours: each of bishopric's urban structures intended to Bishop and the Canonical Chapter was placed separately in their own village. The main subject of research: the town-shields’ planning in Livonia. Research problem: the development of town-shields’ planning at bishoprics in Livonia during the 13th and 14th century have been studied insufficiently. Historians in Latvia often do not take into account studies of urban planning specialists on historical urban planning. Research goal: to determine common and distinctive features of town-shield design in bishoprics of Livonia. Research novelty: town-shield plans of Archbishop’s and their vassals’ residences and capitals in Livonian bishoprics subjected to the Riga Archbishopric are analyzed. Results: study formation of Livonian town-shields’ layout and structure of the 13th and 14th centuries. Main methods: inspection of town-shields in nature, analysis of archive documents, projects, cartographic materials.